'All Over Now?' The Ongoing Relational Consequences of Domestic Abuse through Children's Contact Arrangements. (July 2015) - Morrison, Fiona
<x xml:space="preserve">Abstract</x> The issue of child contact and domestic abuse has gained significant attention in recent years. Research highlights that domestic abuse may not end at the point of separation and the presence of children has been found to be a risk factor for continued abuse. This has raised questions about whether contact in the context of domestic abuse is safe for children and for women. This article presents findings from a qualitative study with 18 children aged eight to 14 years and 16 mothers who had experienced domestic abuse in Scotland. Participants were recruited from domestic abuse support services in both the voluntary and statutory sectors. The research found evidence of the continued abuse of women and children following parental separation that was linked to contact arrangements. Children's contact with their non‐resident fathers often took place amidst an absence of parental communication and cooperation, which was traced to domestic abuse. This left children responsible for navigating the complex and charged dynamic of their parents' relationship. Children reported this negatively, especially for their relationships with their parents. The article, therefore, highlights the importance of considering the impact of the on‐going relational consequences of domestic abuse when considering children's contact arrangements. <boxed-text content-type="pullQuote" id="car2409-blk-0001" position="anchor" orientation="portrait"> 'The presence of children has been found to be a risk factor for continued abuse' </boxed-text> Key Practitioner Messages Domestic abuse may continue following parental separation, with children's contact becoming a central focus for continued abuse. Low levels of parental communication and cooperation following separation may be traced to domestic abuse. Poor parental relations negatively affect child contact. <boxed-text content-type="pullQuote" id="car2409-blk-0002" position="anchor" orientation="portrait"> 'Domestic abuse may continue following parental separation, with children's contact becoming a central focus for continued abuse' </boxed-text>